Effectiveness of Solar Distillation System in Treating Direct Discharge of Car Wash Wastewater - Mohd Azly, Nur Fatin Syahirah; Ena Marlina; Mohd Zaki, Zaizatul Zafflina (International Journal of Integrated Engineering, 2025)
Car wash facilities offer simple alternatives for automobile owners, but by discharging highly contaminated wastewater into rivers, they contribute to environmental degradation. For this study, three different solar still distillation models were developed to treat car wash wastewater, including a standard solar still (Model 1), a painted solar still (Model 2), and a painted solar still combined with sand (Model 3). The objectives of this study included designing and evaluating the effectiveness of these models in producing treated carwash wastewater, as well as assessing the quality of both treated and untreated water in terms of pH, turbidity, COD, BOD, nitrites, nitrates, and zinc. The volume of treated water collected was measured hourly from 9:00 a.m. to 6:00 p.m., and the temperature of both the water and the surroundings was also recorded. The findings indicate that Model 3, which was painted with black paint and sand, performed better in terms of producing effectiveness and water purification. In addition, Model 3 outperformed the other models in terms of effectiveness by producing the highest volume of water and exhibiting the greatest % removal rates for a variety of pollutants, is turbidity (96.0 5%), COD (96.42%), BOD (97.65%), nitrate (60.75%), nitrite (83.33 %) and zinc (93.78 %). The improved thermal mass and heat absorption capabilities of Model 3 were responsible for its higher evaporation rates and overall effectiveness in eliminating contaminants. Car wash wastewater is effectively treated by solar still distillation systems, especially the more efficient ones, such as the painted still with sand. The processed water quality meets the accepted standard, demonstrating the effectiveness and ecological responsibility of solar distillation technology in wastewater treatment.